Analysis of the Factors that Lead to A Discrepancy in Hospital Incomes in Cases of Childbirth by Caesarean Section as Those of the National Healthcare Insurance Patient at the Putra Waspada Hospital Tulungagung - Inggrid Puspitasari Adikarjo; Sentot Imam Suprapto; Ratna Wardani (Universitas STRADA Indonesia, 2024)
The hospital as an advanced health facility collaborates with National Healthcare Insurance Patients (BPJS) using the INA-CBG’S package tarif grouping payment method so that quality control and cost control must be carried out. One of the diagnoses whose costs can be guaranted with BPJS is childbirth with Caesarean Section. The number of Caesarean Section is increasing from year to year and most of the patients are BPJS patients. From the Putra Waspada Hospital Financial Report, there is a negative difference in revenue receipt from Caesarean Section BPJS Patients. The aim of this research is to analyze the factors causing the difference in income revenue hospital in cases of Caesarean Section delivery for National Health Insurance Patients at Putra Waspada Hospital Tulungagung.The sample for this study was 250 medical records of patients who gave birth by caesarean section from January to December 2023.